National survey describing and quantifying students with communication needs. (2nd January 2018) - Andzik, Natalie R.; Schaefer, John M.; Nichols, Robert T.; Chung, Yun-Ching
ABSTRACT: Purpose : Research literature has yet to quantify and describe how students with complex communication needs are supported in the classroom and how special educators are being prepared to offer support. This study sought out special educators to complete a survey about their students with complex communication needs. Method : Over 4, 000 teachers representing 50 states reported on the communicative and behavioral characteristics of 15, 643 students. Teachers described the training they have received and instructional approaches they used. Results : The majority of students were reported to use speech as their primary communication mode. Over half of students utilizing alternative and augmentative communication (AAC) were reported to have non-proficient communication. Teacher training varied across respondents as well as the supports they used to support these students in the classroom. Conclusion : The majority of students with disabilities using AAC when communicating across the nation are not proficiently communicating. Implications and recommendations will be discussed.